Permasalahan dan Dampak dari Implementasi Sistem Pemilu Proporsional Terbuka terhadap Sistem Politik - Muhammad Revan Fauzano Makarim; Khairul Fahmi (Pencerah, 2022)
The holding of elections is a form the implementation of democratic values ​​in which the freedom of expression from citizens for the fulfillment of rights based on the principle for being free to choose and be elected. In its implementation, elections are related to legal aspects and will always experience legal dynamics in the context of each stage of its implementation. The dynamics of the law occur when the implementation of the election is in line with the changing of the legislation governing the implementation of the election which has been regulated periodically for its implementation. Then the enactment of Law Number 7 of 2017 on the Implementation of Elections by the House of Representative with the approval of the President. Stipulation of Law Number 7 of 2017 on the Implementation of Elections shows that there is a legal construction related to the handling of violations and disputes. The violations consist of election crimes, election administration violations, and violations of the code of ethics for election administrators. Then these problems have an impact on its implementation, one of which is in the spotlight is the application of the open proportional electoral system as regulated in Law Number 7 of 2017 on the Open Proportional Election System. The problems in the implementation of this electoral system have an impact on the political system, political parties, and government stability, which then leads to the vulnerability of money politics practices and then causes systematic chaos that disrupts the growth of democracy.